The Effect of Accounting Information System Implementation and Human Resource Competence on the Financial Reporting Quality of Public Service Agencies in the Indonesian Navy - Pratama, Mardiyanto Aris; Faisol, Achmad; achmad, Mohamad (AGUSPATI Research Institute, 2025)
The Public Service Agency (BLU) is a government institution oriented toward public service, operating under a flexible, efficient, and productive financial management system. Several work units within the Indonesian Navy (TNI AL) have been designated as BLUs; however, in practice, they still face various challenges in preparing financial reports, such as reconciliation discrepancies, budget deficits (pagu minus), and account classification errors. Although various accounting information system applications—such as SAKTI, e-Rekon, and BIOS—have been implemented, their effectiveness remains hindered by limited training, low digital literacy, and dependence on internet connectivity. On the other hand, human resource (HR) competency also poses a major issue, as the number of personnel who have received financial training remains very limited. This study aims to analyze the influence of accounting information systems and HR competency on the quality of financial reports, as well as to examine the policies, strategies, and efforts to improve the financial reporting quality of BLUs within the Indonesian Navy. The study population consists of 138 BLU Account Staff personnel in TNI AL, with a sample size of 103 determined using Slovin's formula. Key informants include the Heads of TNI AL Dental and Oral Health Centers (Ladokgi R.E. Martadinata and Yos Sudarso), the Heads of Naval Hospitals (Rumkital Marinir Cilandak, dr. Midiyato S., dr. Mintohardjo, and dr. Ramelan). The research method used is a mixed-method approach. The findings of this study reveal that: 1) The implementation of accounting information systems has a positive and significant effect on the quality of financial reports; 2) HR competency has a positive and significant effect on the quality of financial reports; 3) Accounting information systems and HR competency simultaneously have a positive and significant effect on the quality of financial reports; and 4) The general policy formulated in this research emphasizes improving the quality of financial reporting in TNI AL’s BLUs through enhancing accounting information systems and HR competency. This policy is translated into three key strategies: First, leveraging advancements in science and technology to address integration issues in accounting information systems within TNI AL’s BLUs; Second, enhancing financial IT training through technological developments and inter-agency collaboration; and Third, improving the digital literacy of financial personnel in the Indonesian Navy to meet public transparency demands.